SISTEM PAKAR DETEKSI AWAL PENYAKIT TUBERKULOSIS DENGAN METODE BAYES - Yusuf Ramadhan Nasution; KHAIRUNA KHAIRUNA (KLOROFIL: Jurnal Ilmu Biologi dan Terapan, 2017)
These days, computer technology has been a great need to us humans, especially in medical experts, which evaluated to adopt humans’ ability and knowledge to the computers. So that the computer is capable of solving problems like what an expert is capable of doing. The main purpose of developing the expert system is to substitute all kinds of humans’ knowledge to the technology that it can be useful to the public to solve some specific problems. The application of the expert system made with programming language based on PHP web and MySQL as the database. The method used is Forward Chaining. Expert system can mainly be used to diagnose diseases such as tuberculosis using Bayes method that can diagnose and identify the tuberculosis according to its symptoms.